Physical Education Thematic Games - Dartini, Ni Putu Dwi Sucita; Artanayasa, I Wayan; Satyawan, I Made (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The implementation of the 2013 curriculum gives several changes in learning, one of which was the use of thematic for learning activities in elementary school. Thematic learning is learning that links or combines some subjects that help students understanding the concept completely and meaningfully. This study aims to develop games thematic of physical education with the theme â€œDirikuâ€ for elementary students grade 1. R&D method was used as the method of the study. Besides, the design developed by Borg and Gall was applied as the design. Moreover, this study only focused on Borg and Gall design until the stage of development of the preliminary form of product which was validated by 3 experts, namely content/material expert, design expert, and field practitioners. This study resulted in 8 games thematic of physical education that were spread into 4 sub-themes. The result of the validation test showed that the average percentage of product worthiness was 92.3% in the very good category. It can be concluded that the prototype games thematic of physical education with the theme â€œDirikuâ€ are appropriate to be implemented.